Tumor-induced disruption of the blood-brain barrier promotes host death. - Kim, J.; Chuang, H.C.; Wolf, N.K.; Nicolai, C.J.; Raulet, D.H.; Saijo, K.; Bilder, D. (Developmental Cell, 2021)
Cancer patients often die from symptoms that manifest at a distance from any tumor. Mechanisms underlying these systemic physiological perturbations, called paraneoplastic syndromes, may benefit from investigation in non-mammalian systems. Using a non-metastatic Drosophila adult model, we find that malignant-tumor-produced cytokines drive widespread host activation of JAK-STAT signaling and cause premature lethality. STAT activity is particularly high in cells of the blood-brain barrier (BBB), where it induces aberrant BBB permeability. Remarkably, inhibiting STAT in the BBB not only rescues barrier function but also extends the lifespan of tumor-bearing hosts. We identify BBB damage in other pathological conditions that cause elevated inflammatory signaling, including obesity and infection, where BBB permeability also regulates host survival. IL-6-dependent BBB dysfunction is further seen in a mouse tumor model, and it again promotes host morbidity. Therefore, BBB alterations constitute a conserved lethal tumor-host interaction that also underlies other physiological morbidities.